Ambidexterity, Knowledge Management, and Innovation in Technology Development Zones - Sirkintioğlu Yildirim, Şükran; Atay, Özlem (IGI Global, 2022)
This chapter searches how knowledge management and innovation activities, which enable an advantageous position for firms over their opponents, influence ambidexterity and business performance. These enable firms to gain an advantage over their competitors, concerning ambidexterity and organizational performance. The population for this study comprises firms, operating in technology development zones in Ankara, Turkey. According to the sectoral distribution of the enterprises in the technology development zones, the majority operate in the software sector. No sampling methods were used because the sensus method was adopted. Three hundred sixty high-tech enterprise top managers form the basis of this empirical research. In this study, structural equation modeling was used for testing research model. As a result of the structural equation modeling, it was understood that firms' knowledge management and innovation usage preferences have a positive impact on ambidexterity and organizational performance. This outcome is important for firms to gain a competitive advantage.
Keywords: 9. Industry and infrastructure; 8. Economic growth